The effectiveness of cognitive behavioral therapy on marital conflict and coping strategies of women involved in emotional divorce - Amirkiani, Amirhomayoun; Ahmadi, Zohreh; Jafari, Khatereh; Rashidi Asl , Shokooh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The purpose of this study was to determine the effectiveness of cognitive behavioral therapy on marital conflict and coping strategies of women involved in emotional divorce. Methods: The current research method was conducted as a semi-experimental study with a pre-test and post-test design along with a control group with a follow-up period. The statistical population included all the women eligible for emotional divorce in Tehran who referred to the Atiyeh Psychology Clinic in 2021, from which 30 people were selected as convenience and randomly selected and in the experimental group (15 people) and witnesses (15 people) were replaced. The data were collected using Barati and Sanai’s Marital Conflict Questionnaire (1999), Gutman’s Emotional Divorce Questionnaire (2008), Lazarus and Folkman’s Coping Strategies Questionnaire (1984) in the pre-test, post-test and follow-up stages. It has been achieved. Cognitive-behavioral therapy protocol was performed in 8 sessions (one session per week) for 90 minutes. To analyze the results, repeated measurement variance analysis method and SPSS.22 software were used. Results: The results indicated that cognitive-behavioral therapy in reducing marital conflict (F=44.25, P<0.001), emotion-oriented coping strategies (F=30.53, P<0.001) P) and increase in problem solving strategy (F=33.86, P<0.001) of women involved in emotional divorce was effective and this effect was lasting until the follow-up period. Conclusion: It can be concluded that cognitive behavioral therapy is effective on marital conflict and coping strategies of women involved in emotional divorce and this treatment can be used to reduce the problems of women involved in emotional divorce.